Fluoride concentration and labeling requirements of mineral bottled water from Brazil - Daniele Esteves Pepelascov; Mitsue Fujimaki; Jaime Aparecido Cury; Cínthia Pereira Machado Tabchoury; Jorge Ulises Guerra Villalobos; Raquel Sano Suga Terada (Fundação Oswaldo Cruz (FIOCRUZ), 2017)
Introduction: Mineral waters usually contain natural fluoride (F) in their composition, but the benefits and risks of the concentrations found are not clearly informed. Objective: The aim of this study was to determine the F concentration in mineral bottled waters and to check if the concentrations found: (1) matched with those informed on the label and (2) were coherent with claims on the label about the anticaries benefits and the risks of fluorosis. Method: Two batches of twenty brands, in all forms of commercial presentation found, were analyzed. F concentration was determined in duplicate using ion-specific electrode. Labels were analyzed regarding the F concentration informed. Results: Mean F concentration was 0.08 ppm, ranging from <0.05 to 0.33 ppm. The F concentrations found were generally consistent with the concentrations informed. None of the waters analyzed presented F concentration either to have anticaries effect or fluorosis risks. However, 19 of the 20 brands evaluated highlighted on the labels that their products were "fluoridated bottled water", suggesting that the concentrations found were "optimal" for the balance benefits/risks of F use. Conclusions: In order to avoid misleading information to the consumers, the current regulations on the composition of F in bottled water as well as their labeling should be revised.